Post-COVID-19 families: how early educators facilitate socio-emotional development in their students during the COVID-19 pandemic" - Klutse, Adelaide (Kansas State University, 2022)
The COVID-19 virus through its mode of transmission and needed adaptations influenced human interaction in several ways which include for the early educator activities known to facilitate socio-emotional development. This study assesses the extent to which professional development, perceived stress, comfort with safety practices, and quarantine status related to teachers’ social-emotional development practices (SEDP) in the Early Care and Education (ECE) setting during the COVID-19 pandemic. A cross-sectional survey of early educators working with children aged 0-5 across the U.S. was conducted. The relationships among variables were assessed through hierarchical regression analysis. Results revealed that there was a significant relationship between high levels of comfort with safety practices and increased socio-emotional development practices. Additionally, a significant relationship between the teachers' level of stress and increased socio-emotional development practices existed. These findings suggest that during the COVID-19 pandemic, early educator SEDP were related to their stress levels and their feelings of comfort. Limitations of the study and implications for policy, practice, and research are provided.
Keywords: COVID-19; Early childhood education; Socio-emotional development; Safety practices; Stress